Fracture Properties of Nash Point Shale as a Function of Orientation to Bedding. Issue 10 (9th October 2018) - Forbes Inskip, Nathaniel D.; Meredith, Philip G.; Chandler, Michael R.; Gudmundsson, Agust
Abstract: Understanding how fracture networks develop in shale formations is important when exploiting unconventional hydrocarbon reservoirs and analyzing the integrity of the seals of conventional and carbon capture and storage reservoirs. Despite this importance, experimentally derived fracture data for shale remains sparse. Here we characterize shale from Nash Point in South Wales, United Kingdom, in terms of ultrasonic wave velocities, tensile strength, and fracture toughness ( K Ic ). We measure these properties in multiple orientations, including angles oblique to the three principal fracture orientations—Short‐transverse, Arrester, and Divider. We find that the Nash Point shale is mechanically highly anisotropic, with tensile strength and K Ic values lowest in the Short‐transverse orientation and highest in the Arrester and Divider orientations. Fractures that propagate in a direction oblique or normal to bedding commonly deflect toward the weaker Short‐transverse orientation. Such deflected fractures can no longer be considered to propagate in pure mode‐I. We therefore present a method to correct measured K Ic values to account for deflection by calculating mode‐I and mode‐II deflection stress intensities ( K Id and K IId, respectively). Because of the mixed‐mode nature of deflected fractures, we adopt a fracture ( G c ) energy‐based approach that allows analysis of critical fracture propagation conditions for both deflected and undeflected fractures in all orientations. We find that G c increases as the angle from the Short‐transverse plane increases. We conclude that a modified elliptical function, previously applied to tensile strength and K Ic, can be used to estimate values of G c at angles between the Short‐transverse and Arrester orientations. Key Points: Measurements of tensile strength and mode‐I fracture toughness ( K Ic ) show that Nash Point shale is mechanically highly anisotropic We find that a fracture energy ( G c ) approach is more suitable than using K Ic alone, because it allows analysis of mixed mode fracture propagation An elliptical function can be used to estimate G c for fractures propagating at angles between the Short‐transverse and Arrester directions